Financial Sector Development and the Millennium Development Goals - Claessens, Stijn (Washington, DC: World Bank, 2012)
This study investigates the relationship between financial sector development and progress in reaching the Millennium Development Goals (MDGs). It assesses the contribution of countries' financial sector development to achieving the MDGs. The focus is on the relationships between financial development and economic welfare and growth, and the following four MDG-themes: Poverty, Education, Health, and Gender Equality. In doing so, the book reviews the theoretical channels, surveys existing empirical evidence - both cross-country and case study evidence, and provides new evidence. Financial Sector Development and the Millennium Development Goals finds that financial development is an important driver for economic welfare in that it reduces the prevalence of income poverty and undernourishment. In addition, new evidence is provided of a positive association between financial development and health, education, and gender equality.